Age Determination and Growth Parameters of Lutjanus bohar (Forsskal, 1775) in Jeddah Fisheries, Saudi Arabia - Gabr, Mohamed; Almuwlad, Abeer; Alsulami, Lafi (Journal of King Abdulaziz University: Marine Sciences, 2021)
Age-based life history parameters: the asymptotic length (L∞), the growth coefficient (K) and the hypothetical age at zero length (t0), for Lutjanus bohar in Jeddah fisheries were estimated. Scales were used for age determination and measurements, and the back-calculated lengths-at-ages were calculated using the body proportional formula (BPH). The growth of L. bohar is isometric where the length-weight relationship could be described by the power equation: W = 0.0125 L3.05 (R2 = 0.99) for males, W = 0.01571 L3.00 (R2 = 0.98) for females, and W = 0.0142 L3.04 (R2 = 0.99) for combined sexes. The Scale radius (S) total length (L) relationship could be described by the linear form: L = 5.52 S - 0.41 (R2 = 0.953) for males, L = 5.64 S - 0.85 (R2 = 0.945) for females, and L = 5.60 S - 0.39 (R2 = 0.948) for combined sexes. The growth parameters were estimated to be: L¥ = 89.38 cm, K = 0.123 year-1, and to = -1.04 year for males; L¥ = 90.68 cm, K = 0.121 year-1, and to = -1.05 year for females; and L¥ = 90.17 cm, K = 0.122 year-1, and to = -1.04 year for pooled data. The performance index of growth in length ' Ф' ' was found to be 3.0 for both males and females. The maximum age (life span) was estimated to be 23.8 year for females and 22.8 year for males, which indicate that L. bohar is a long-lived species.